The gut-brain axis: potential reshaping the future of anti-NMDAR encephalitis treatment - Shen, Changchang; Xie, Yinyin; Xie, Yi; Wang, Lina; Han, Aoya; Zhou, Xinru; Zhang, Shijie; Fu, Xili; Xie, Nanchang (Frontiers in Immunology, 2025)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a type of autoimmune encephalitis with a high disability rate. However, its pathogenesis remains unclear and warrants further elucidation to facilitate the development of effective treatment strategies. The gut microbiota can increase the permeability of the intestinal and blood-brain barriers by altering the levels of beneficial bacterial metabolites and pro-inflammatory factors. These alterations facilitate the migration of inflammatory factors and pathogenic autoantibodies to the central nervous system, thereby affecting the progression of anti-NMDAR encephalitis. Therefore, interventions targeting the gut microbiota may be effective for regulating the pathogenesis of anti-NMDAR encephalitis. In this review, we discuss the association between an altered gut microbiota and associated changes in metabolite levels in patients with anti-NMDAR encephalitis. To our knowledge, this review is the first to outline the effects of the gut microbiota on cytokine levels in the blood and cerebrospinal fluid of patients with anti-NMDAR encephalitis, which may provide a new therapeutic perspective for this fatal disease.